KEMAMPUAN MAHASISWA DALAM MENDETEKSI FRAUD - Ni Luh Putu Widhiastuti; Putu Diah Kumalasari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
This study aimed to determine the ability of students to detect fraud by using variables of student’s motivation, academic achievement, involvement in auditing lectures and the ability to detect fraud. The study was conducted on all students of the undergraduate program of the accounting department at the Faculty of Economics and Business Mahasaraswati Denpasar University. This study used purposive sampling method and obtained 74 respondents. The analysis technique used was the multiple linear regression analysis. The results suggested that student’s motivation had effect on the involvement in auditing lectures, while academic achievement had no effect on the involvement in auditing lectures. Meanwhile, involvement in auditing lectures had effect on the ability to detect fraud, while student’s motivation and academic achievement had no effect on the ability to detect fraud. Intervening analysis results suggested that the involvement in auditing lectures as an intervening variable that effected the student’s motivation on the ability to detect fraud, meanwhile, the involvement in auditing lectures was not an intervening variable that effected the academic achievement on the ability to detect fraud. This study provides encouragement for the institutions, in this case the universities, to improve the ability of its students in detecting fraud. Moreover, this study provides insight in auditing field research.